A Study of Living Megalithic Tradition Among the Gond Tribes, District – Nuaparha, Odisha. (1st September 2015) - Mendaly, S.
The present paper deals with the existence and continuation of living megalith tradition among the Gond tribe in Nuaparha district of Odisha. The mortuary practice of different tribal community have given many ethnographical data, which is used as a primary source to reconstructing the past social and cultural history of megalithic people.